Citreoviridin induces ROS-dependent autophagic cell death in human liver HepG2 cells. (1st March 2015) - Liu, Ya-Nan; Wang, Yue-Xia; Liu, Xiao-Fang; Jiang, Li-Ping; Yang, Guang; Sun, Xian-Ce; Geng, Cheng-Yan; Li, Qiu-Juan; Chen, Min; Yao, Xiao-Feng
Abstract: Citreoviridin (CIT) is one of toxic mycotoxins derived from fungal species in moldy cereals. Whether CIT exerts hepatotoxicity and the precise molecular mechanisms of CIT hepatotoxicity are not completely elucidated. In this study, the inhibitor of autophagosome formation, 3-methyladenine, protected the cells against CIT cytotoxicity, and the autophagy stimulator rapamycin further decreased the cell viability of CIT-treated HepG2 cells. Knockdown of Atg5 with Atg5 siRNA alleviated CIT-induced cell death. These finding suggested the hypothesis that autophagic cell death contributed to CIT-induced cytotoxicity in HepG2 cells. CIT increased the autophagosome number in HepG2 cells observed under a transmission electron microscope, and this effect was confirmed by the elevated LC3-II levels detected through Western blot. Reduction of P62 protein levels and the result of LC3 turnover assay indicated that the accumulation of autophagosomes in the CIT-treated HepG2 cells was due to increased formation rather than impaired degradation. The pretreatment of HepG2 cells with the ROS inhibitor NAC reduced autophagosome formation and reversed the CIT cytotoxicity, indicating that CIT-induced autophagic cell death was ROS-dependent. In summary, ROS-dependent autophagic cell death of HpeG2 cells described in this study may help to elucidate the underlying mechanism of CIT cytotoxicity. Highlights: Citreoviridin increased autophagosome formation in HepG2 cells. Citreoviridin induced autophagic cell death in HepG2 cells. ROS played a vital in the citreoviridin-induced autophagic cell death.